Cardiac surgeryLong-term follow-up in adult patients after Fontan operations - Tomkiewicz-Pająk, Lidia; Hoffman, Piotr; Trojnarska, Olga; Bednarek, Jacek; Płazak, Wojciech; Pająk, Jacek Władysław; Olszowska, Maria; Komar, Monika; Podolec, Piotr Stanisław (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2013)
Aim of the study : The aim of the retrospective study was to determine the prevalence of late complications in adult patients after the Fontan operation (FO). Material and methods: Forty-eight Caucasians patients after staged FO (26 men, 22 women) aged between 18 and 40 years (mean 23 ±5 uears) were included in the study. The evaluation included echocardiograms, electrocardiograms, cardiopulmonary exercise tests (CPX), oxygen saturation and medical history and laboratory tests. Based on the postoperative time, the patients were divided into three groups: up to 15 years, between 16 and 20 years and above 20 years after surgery. Results : Thromboembolism was present in 10 patients (21%). Supraventricular tachycardias were noted in 10% of subjects, ventricular tachycardia in 4% of patients. Mean oxygen saturation was 89%, cyanosis was seen in 25% of patients. Protein-losing enteropathy appeared in 4%. While analyzing parameter values in patients belonging to various postoperative time groups, highly significant differences were noted in VO 2peak , VO 2 %N, SaO2 (oxygen saturation), and HCT. Along with an increased postoperative period, the SV function deteriorated (x 2  p = 0.001, Fisher p = 0.001) and a higher degree of systemic atrioventricular valve regurgitation was detected (x 2  p < 0.001, Fisher p < 0.001). Conclusions: In adults after the Fontan operation, the systolic function of a single ventricle deteriorates with time, atrioventricular valve regurgitation increases and exercise tolerance is reduced. Cyanosis is increased and hematocrit levels are elevated. Such patients require regular assessment in specialist centers for adult patients with congenital heart defects.